A Comparison of Active and Passive Virtual Reality Exposure Scenarios to Elicit Social Anxiety - Yoones A. Sekhavat; Poorya Nomani (Serious Games Society, 2017)
Social phobia is an anxiety disorder that results in an excessive and unreasonable fear of social situations. As a safe and controlled tool, Virtual Reality Exposure Therapy (VRET) has been used to treat anxiety disorders and phobias. This paper aims to study whether VRET with active scenarios can challenge a person more than passive scenarios. By comparing participants who were exposed to active and passive scenarios in VRET, we show that active scenarios are more effective than passive scenarios to elicit social anxiety in healthy participants. We focus on eliciting social anxiety and creating the sense of presence as two parameters enhancing the efficacy of VRET scenarios.